The effect of ficus deltoidea var. kunstleri (mas cotek) supplementation on skeletal of rats fetus / Darnah Hasim - Hasim, Darnah (2019)
Ficus deltoidea (F. deltoidea) traditionally known as ‘Mas Cotek’ in Malaysia and has a long history of traditional medicine used by Malays to treat various of diseases and as health tonic. Data on F.deltoidea safety for pregnant women and their babies are still not available. The study was conducted to study the effect of aqueous extract of Ficus deltoidea’s leaves supplementation following 15 days on skeletal of rats fetus. Fifteen pregnant Sprague Dawley rats were randomly sorted into non-supplemented control and supplemented groups (250 and 500 mg/kg/day) of standardized aqueous extract of F.deltoidea on gestation days 6-20 (n=5). At gestation day 21, caesarean section was performed and half of fetuses from each litter with a total of 90 fetuses (n=30) were cleared and stained with Alizarin Red S for skeleton evaluation. The result showed some skeletal variation however Ficus deltoidea did not affect the occurrence of skeletal abnormalities. Standardized aqueous extract of Ficus deltoidea increase a few skeleton variation such as absence of hyoid body, dumbbell shaped thoracic vertebra and incomplete ossification of frontal and fingers. These skeletal abnormalities are non-dose dependent manner. Overall the result of the current findings suggested that supplementation of Ficus deltoidea aqueous extract did not result in any fetal death, prenatal growth retardation, or structural malformation in their offspring and probably safe to be taken as it does not have any teratogenic risks.